2020
DOI: 10.1097/adm.0000000000000533
|View full text |Cite
|
Sign up to set email alerts
|

Association of Marijuana, Mental Health, and Tobacco in Colorado

Abstract: Objectives: Marijuana's evolving legality may change marijuana use patterns in adults. Co-use of marijuana and tobacco are strongly associated, and populations with mental health disorders are disproportionately likely to use either substance, but neither association has been assessed in the context of legal recreational marijuana. We assessed the associations of tobacco smoking with marijuana use and with mental health disorders in Colorado in 2015. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Temporary escalation in heart rate due to peripheral stimulation has been noticed by Frewer (1990) after consumption of betel quid. Various researchers observed that people with mental health disorders are more likely to smoke tobacco (Stewart et al 2020).…”
Section: Effects On Mental Healthmentioning
confidence: 99%
“…Temporary escalation in heart rate due to peripheral stimulation has been noticed by Frewer (1990) after consumption of betel quid. Various researchers observed that people with mental health disorders are more likely to smoke tobacco (Stewart et al 2020).…”
Section: Effects On Mental Healthmentioning
confidence: 99%